Perkembangan Usaha Bubuk Kopi Yunizar Taratak di Nagari Kubang Kecamatan Guguak Kabupaten Lima Puluh Kota Tahun 2000-2022 - Tiara Armelia; Rusdi Rusdi (Jurnal Kronologi, 2023)
ABSTRAK In 1998, after the monetary crisis, the Yunizar coffee powder industry in Taratak Nagari Kubang did not go out of business and is still surviving today. In 2000, unhealthy competition between coffee sellers and other coffee entrepreneurs. In 2000 Yunizar began packing the coffee powder he produced with the brand name or product name of the original coffee powder Yunizar Taratak Kubang, Guguak District, Lima Puluh Kota Regency until now in 2022 with the aim of avoiding fraud in businesses carried out by irresponsible individuals. The results of the study show that: The development of the Yunizar Taratak coffee powder business in 2000-2022 that: (a) The 2000-2007 Development Period occurred with a monetary crisis, and unhealthy competition among coffee businesses, (b) The 2007-2014 Development Period of coffee raw materials was sufficient expensive and rare, (c) Development Period 2014-2022 there was no support from the government, traditional tools changed to modern ones, and the issuance of Business Identification Numbers (NIB) was recommended by the author. Keywords: Development, Business, Coffee Powder, Nagari. ABSTRAK Tahun 1998 setelah krisis moneter, industri gula kopi Yunizar di Taratak Nagari Kubang tidak mengalami gulung tikar dan masih bertahan sampai sekarang. Pada tahun 2000 persaingan yang tidak sehat diantara penjual kopi dengan banyak pengusaha kopi lain. Pada tahun 2000 Yunizar mulai mengemas bubuk kopi yang diproduksinya dengan merk atau nama produk bubuk kopi asli Yunizar Taratak Kubang Kecamatan Guguak Kabupaten Lima Puluh Kota hingga sekarang tahun 2022 dengan tunjuan menghindari kegagalan dalam usaha yang dilakukan oleh oknum yang tidak bertanggung jawab. Hasil penelitian menunjukkan bahwa: Perkembangan usaha bubuk kopi Yunizar Taratak Tahun 2000-2022 bahwa: (a) Perkembangan Periode Tahun 2000-2007 terjadinya krisis monenter, dan persaiangan tidak sehat sesama usaha kopi, Kata Kunci: Perkembangan, Usaha, Bubuk Kopi, Nagari.